Detection and Development of Infestation Rate of Aphelenchoides besseyi on Various Rice Seed Varieties - Nikmatul 'Azizah; Siwi Indarti; Ani Widiastuti; Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2019)
Aphelenchoides besseyi is a seed borne nematode caused white tip disease. Infested rice seeds are beneficial inoculum source forA. besseyi widespread. The objective of this research was to determine the occurence and development of symptom level caused by A. besseyi in rice seed varieties. The research was done by detecting A. besseyi in rice seed using Hoshino and Togashi method and counting the nematode population in the seed; observing the incubation time and measuring disease incidence every week. The result revealed that A. besseyi was found in 16 of 17 varieties, i.e. R1 IR64, R2 IR64, R3 IR64, R1 Situbagendit, R2 Situbagendit, Inpari 33, R1 Memberamo, R2 Memberamo, R3 Memberamo, R1 Way Apo Buru, R2 Way Apo Buru, Mekongga, Pepe, Ketan, Sintanur, and Ciherang.A. besseyi infection increased every week in many varieties depend on quantitative (statistics) and qualitative (symptom) indicators. There were 4 varieties have to be investigate further because they were infested by A. besseyi>30 nematodes/100 seeds, i.e. R1 Way Apo Buru, R1 Situbagendit, Ketan and R3 IR 64. A practice that is also required is the elimination of A. besseyi inoculum in rice seed before cultivate.